Rhetorical Agency: Mind, Meshwork, Materiality, Mobility - Belikian, Les (punctum books, 2017)
In recent accounts of rhetoric's storied productivity, commentators have implied, along systematically Kantian lines, albeit with the occasional protestation, that agency must be coextensive with subjectivity. But is that all there is (to 2,500 years' worth of hypothesizing about the ways in which communication might promote social change)? Les Belikian's answer, drawing not only on traditional and contemporary rhetorical studies but also on Deleuzean thinking, actor-network theory, and object-oriented ontology, takes the form of a quadruply contrarian thesis: Rhetorical agency inheres, irreducibly so, in subjectivity, in conventionality, in transcendence, and in materiality, all of which are themselves always under production.